The pivotal role of ECG in cardiomyopathies - Silvetti, Elisa; Lanza, Oreste; Romeo, Fabiana; Martino, Annamaria; Fedele, Elisa; Lanzillo, Chiara; Crescenzi, Cinzia; Fanisio, Francesca; Calò, Leonardo (Frontiers in Cardiovascular Medicine, 2023)
Cardiomyopathies are a heterogeneous group of pathologies characterized by structural and functional alterations of the heart. Recent technological advances in cardiovascular imaging offer an opportunity for deep phenotypic and etiological definition. The electrocardiogram (ECG) is the first-line diagnostic tool in the evaluation of both asymptomatic and symptomatic individuals. A learned and careful interpretation of the ECG features can raise suspicion of the presence of a cardiomyopathy, identify diagnostic "red flags" useful for orienting the diagnosis toward specific forms, and provide useful tools for risk stratification. The purpose of this review is to emphasize the important role of the electrocardiogram in the diagnostic work-up, describing the main ECG findings of different cardiomyopathies.